(untitled) (Indian Journal of Animal Production and Management, 2024)
Small ruminants play a significant role in economy of India, contributing to the production of meat, milk, fibre, and skins. The rearing of these small ruminants serves as a crucial source of income and employment for a substantial portion of the population, with the majority being comprised of impoverished and small-scale farmers. Studies addressing the challenges affecting the welfare of small ruminants have been relatively scarce. Additionally, research on strategies aimed at mitigating the adverse effects of environmental factors and management practices on small ruminant welfare has been limited. This review aims to discuss the challenges that impact the welfare of small ruminants across various farming systems. These challenges include extreme climatic conditions and seasonal fluctuations, inadequate space and premises layout, microclimate control, health problems and many more. Different mitigation strategies are highlighted that can be adopted for improving small ruminant welfare under different production systems.